(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Teeth have been used as excellent bio-monitoring tool as incorporation of trace elements in dental tissues is a well regulated phenomenon. Measuring elemental composition in human bones and teeth has been promisingly used for identification of age, sex, species and pollutant exposures. To supplement the available scientific data on elemental composition of human tooth for forensic anthropological purposes, present study was formulated to estimate sexual dimorphism in modern molar teeth based on their elemental composition quantified from using WD-XRF technique. A total of 132 freshly extracted permanent molar teeth were collected from patients (10- 74 years) who had visited the hospital for orthodontic reasons in the year 2017. The average mean values of almost all the elements were found comparatively higher in males than the females; sulphur and strontium exhibiting statistically significant sexual differences between the two sexes. The results of the univariate DFA analysis showed that strontium (Sr) and potassium (K) were the most and least sexually dimorphic elements, respectively, showing that univariate elemental analysis is not useful for determination of sex of any unknown tooth sample for forensic purposes. From MVDFA of all elements, the sulphur, strontium, magnesium and silicon were selected as the best element which could identify sex of only 75.8% teeth (58.5% males and 89.9% females). Though elemental profile of teeth has little scope for forensic sex determinations, it can supplement other observations and analyses as corroborative evidence. It can become an effective sex determination tool in forensics if the investigators have information about dietary history and nutritional status of the affiliated population group and larger database of elemental composition of different biological evidences of human origin including teeth.